An AI-powered data curation and publishing virtual assistant: usability and explainability/causability of, and patient interest in the first-generation prototype - van Mierlo, Rutger; Liang, Wenjie; Norak, Kerli; Kargl, Michaela; Maasik, Mall; Bynens, Anne-Lore; Plass, Markus; Kreuzthaler, Markus; Benedikt, Martin; Hochstenbach, Laura; van 't Hof, Arnoud; Celebi, Remzi; et al. (Frontiers in Digital Health, 2025)
IntroductionEnsuring high quality and reusability of personal health data is costly and time-consuming. An AI-powered virtual assistant for health data curation and publishing could support patients to ensure harmonization and data quality enhancement, which improves interoperability and reusability. This formative evaluation study aimed to assess the usability of the first-generation (G1) prototype developed during the AI-powered data curation and publishing virtual assistant (AIDAVA) Horizon Europe project.MethodsIn this formative evaluation study, we planned to recruit 45 patients with breast cancer and 45 patients with cardiovascular disease from three European countries. An intuitive front-end, supported by AI and non-AI data curation tools, is being developed across two generations. G1 was based on existing curation tools and early prototypes of tools being developed. Patients were tasked with ingesting and curating their personal health data, creating a personal health knowledge graph that represented their integrated, high-quality medical records. Usability of G1 was assessed using the system usability scale. The subjective importance of the explainability/causability of G1, the perceived fulfillment of these needs by G1, and interest in AIDAVA-like technology were explored using study-specific questionnaires.ResultsA total of 83 patients were recruited; 70 patients completed the study, of whom 19 were unable to successfully curate their health data due to configuration issues when deploying the curation tools. Patients rated G1 as marginally acceptable on the system usability scale (59.1 ± 19.7/100) and moderately positive for explainability/causability (3.3–3.8/5), and were moderately positive to positive regarding their interest in AIDAVA-like technology (3.4–4.4/5).DiscussionDespite its marginal acceptability, G1 shows potential in automating data curation into a personal health knowledge graph, but it has not reached full maturity yet. G1 deployed very early prototypes of tools planned for the second-generation (G2) prototype, which may have contributed to the lower usability and explainability/causability scores. Conversely, patient interest in AIDAVA-like technology seems quite high at this stage of development, likely due to the promising potential of data curation and data publication technology. Improvements in the library of data curation and publishing tools are planned for G2 and are necessary to fully realize the value of the AIDAVA solution.